2015
DOI: 10.1109/tie.2015.2455518
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal Versus Square-Wave Current Supply of PM Brushless DC Drives: A Convenience Analysis

Abstract: Permanent-magnet (PM) brushless direct current (BLDC) drives are utilized in a variety of applications because of their inherent features and would be even more utilized if their torque performance could be improved. Indeed, when supplied with square-wave currents, the torque-speed characteristic undergoes a drop at high speeds, and a significant torque ripple arises at both low and high speeds due to the commutation phenomena. In this paper, the sinusoidal current supply of the PM BLDC motors is investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The work in [10] minimizes the torque ripple by selective elimination of torque harmonics achieved through the supply of the motor phases with a sinusoidal-like current waveform. The sinusoidal current supply outperforms the real squarewave current supply over almost the speed range [11]. Summarizing the above studies, it can be concluded that the overlap commutation and conduction modes combination will extend commutation time, increase switching losses, and decrease efficiency [4].…”
Section: Description Of the Traditional Swcmentioning
confidence: 83%
See 2 more Smart Citations
“…The work in [10] minimizes the torque ripple by selective elimination of torque harmonics achieved through the supply of the motor phases with a sinusoidal-like current waveform. The sinusoidal current supply outperforms the real squarewave current supply over almost the speed range [11]. Summarizing the above studies, it can be concluded that the overlap commutation and conduction modes combination will extend commutation time, increase switching losses, and decrease efficiency [4].…”
Section: Description Of the Traditional Swcmentioning
confidence: 83%
“…The main studies on reducing the commutation torque ripple include overlap commutation, two-phase and three-phase conduction modes combination, adding power supply circuits in front of the three phase inverter, modifying power topology, decoupling control, and the sinusoidal current supply [2][3][4][5][6][7][8][9][10][11]. Overlapping commutation and duty pulse width modulation (PWM) optimization are adopted to reduce the torque ripple in [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the sinusoidal-wave current is always used to drive the sinusoidal back-EMF motor, which is called as PM BLACM in general [17][18][19][20]. These two current waveforms and their improvements have been used for several different motors [21][22][23][24][25][26][27][28]. In [21], a third-harmonic was injected into the sinusoidal-wave current for dual three-phase permanent magnet machines to improve the output torque.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent Magnet In-wheel Motor (PMIM) fed by sinusoidal-current requires rotor position information with highresolution from Hall-effect sensors. High-resolution position and velocity estimation of PMIM with Hall-effect sensors and its low-cost vector control drives have been a heated discussion in the research area in recent years [3,4,5]. However, in most proposed methods, the fault states of the Hall-effect sensors signals are seldom considered, and few research studies on fault diagnostic and compensations methods are able to overcome the failures of Hall-effect sensors.…”
Section: Introductionmentioning
confidence: 99%